STUDENTS' SCIENTIFIC SOCIETY IN CAREER-GUIDANCE MOTIVATION FOR MEDICAL STUDENTS - I. Tokarchuk (Bogomolets National Medical University, 2015)
Summary. Creative atmosphere of medical education helps to improve its quality and provides opportunities to conduct scientific research for young specialists. Progresses of personality's creative potential and creative self-realization in professional activities are very important conditions for specialist's personality development. The period analyzed started with the second year of training, when students usually begin to attend surgical department. It showed the increasing interest during studying and great role of surgical scientific student's society for career- guidance.